Estimation of palladium-103 radionuclide producibility at the cyclotron CV-28 for nuclear medicine - Petrusenko, Yu.T.; Lymar’, A.G.; Nikolaichuk, L.I.; Ponomarenko, T.A.; Tutubalin, A.I.; Shepelev, A.G. (Вопросы атомной науки и техники, 2009)
Consideration is given to the possibility of 103P d radionuclide production in nuclear reactions on protons and deuterons at the cyclotron CV −28, for a subsequent use of the radionuclide in medicine, in particular, for brachytherapy. Activity estimates of 103P d produced on both the internal and external targets of the cyclotron CV − 28 are given. The energy transferred by the proton/deuteron beam to the target under irradiation is determined. Possible ways of heat removal from the target substrate are considered.